Comparative effectiveness of oral drug therapies for lower urinary tract symptoms due to benign prostatic hyperplasia: a systematic review and network meta-analysis. - Xinghuan Wang; Xiao Wang; Sheng Li; Zhe Meng; Tao Liu; Xinhua Zhang (PLoS ONE, 2014)
Introduction Lower urinary tract symptoms (LUTS) due to benign prostatic hyperplasia (BPH) are common in elder men and a number of drugs alone or combined are clinically used for this disorder. But available studies investigating the comparative effects of different drug therapies are limited. This study was aimed to compare the efficacy of different drug therapies for LUTS/BPH with network meta-analysis. Materials and methods An electronic search of PubMed, Cochrane Library and Embase was performed to identify randomized controlled trials (RCTs) comparing different drug therapies for LUTS/BPH within 24 weeks. Comparative effects were calculated using Aggregate Data Drug Information System. Consistency models of network meta-analysis were created and cumulative probability was used to rank different therapies. Results A total 66 RCTs covering seven different therapies with 29384 participants were included. We found that α-blockers (ABs) plus phosphodiesterase 5 inhibitors (PDE5-Is) ranked highest in the test of IPSS total score, storage subscore and voiding subscore. The combination therapy of ABs plus 5α-reductase inhibitors was the best for increasing maximum urinary flow rate (Qmax) with a mean difference (MD) of 1.98 (95% CI, 1.12 to 2.86) as compared to placebo. ABs plus muscarinic receptor antagonists (MRAs) ranked secondly on the reduction of IPSS storage subscore, although monotherapies including MRAs showed no effect on this aspect. Additionally, PDE5-Is alone showed great effectiveness for LUTS/BPH except Qmax. Conclusions Based on our novel findings, combination therapy, especially ABs plus PDE5-Is, is recommended for short-term treatment for LUTS/BPH. There was also evidence that PDE5-Is used alone was efficacious except on Qmax. Additionally, it should be cautious when using MRAs. However, further clinical studies are required for longer duration which considers more treatment outcomes such as disease progression, as well as basic research investigating mechanisms involving PDE5-Is and other pharmacologic agents alleviate the symptoms of LUTS/BPH.